Exploring the role of peer review in computational thinking development among pre-service teachers - Voon, Xin Pei; Wong, Su Luan; Wong, Lung Hsiang; Md Khambari, Mas Nida; Syed-Abdullah, Sharifah Intan Sharina (Asia-Pacific Society for Computers in Education, 2026)
Computational thinking can be interpreted as a cognitive process that provides a new paradigm for higher-order thinking about successfully solving problems posed in a technology-mediated teaching and learning context. Peer review has been employed as an effective learning strategy to enhance cognitive practices such as critical thinking, reflection practices and collaborative experiences. A qualitative case study was conducted to explore the role of peer review as a learning strategy of computational thinking among pre-service teachers. The peer comments were coded by adopting a coding scheme of comments, and the interview transcripts were analysed to investigate the significance of the peer-review process and student perceptions of what is most beneficial. Each student was required to design a lesson by integrating the computational thinking facets into their lesson plan. Upon submitting the lesson plan, they were engaged in a blind review process. Individual student reviews the lesson designed by their peers and provides their comments. By adapting a peer-review cognitive process model, this article provides evidence that the peer-review process played a critical role in facilitating pre-service teachers' computational thinking, particularly problem-solving competencies. The findings indicate that peer review strategy can facilitate computational thinking by enhancing pre-service teachers' higher-order thinking through constructing and providing critical feedback to their peers. The students perceived the peer-review process was beneficial in improving their computational thinking-integrated lesson design. However, it was suggested that the students be informed about the purposes and learning benefits of the peer-review process to improve their learning experience.